Systematization and Classification of ‘Soft Law’ Sources in the Financial Law of Russia - EREMIN, Sergey; LUKICHEV, Konstantin; KAMOLOV, Sergey; MIGACHEVA, Elena; VERSHILO, Tatiana (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
The aim of this work is to develop a classification of soft law sources in the financial law of the Russian Federation and their systematization. The study revealed the fact that Russian fiscal authorities and courts have increasingly turned to the documents of the Organization for Economic Co-operation and Development (OECD) especially in connection with the taxation issues. The study discloses an important soft-law feature – to transform to the financial law and become legally binding. It was adjusted that there are a large number of soft law legislative acts, regarding transfer pricing and double taxation avoiding have been passed by international organizations and bodies nowadays. These acts are being used a lot in the Russian financial law. The study investigates the most important soft law act – OECD Model Tax Convention and its comments - issued by the Organization for Economic Co-operation and Development (OECD). According to the result of the study, the classification of soft-law acts was carried out. The classification is based on the following criteria: functions, goals, scope (influence), bill passing authorities, types of adopted acts, bill scope. The developed classification and systematization ensure a more efficient and uniform application of the soft law sources in practice. At work there were used general and specific scientific research methods: method of interpretation of the rules of laws, system-structural and formal-legal methods, logical method.